МОДЕЛИРОВАНИЕ НЕЛИНЕЙНОГО СОПРОТИВЛЕНИЯ ЭЛЕКТРОИСКРОВОЙ НАГРУЗКИ ДЛЯ СИНТЕЗА ЦЕПИ РАЗРЯДА КОНДЕНСАТОРА ПО ВРЕМЕННЫМ ХАРАКТЕРИСТИКАМ - Щерба , А.А.; Супруновская , Н.И.; Иващенко , Д.С. (Інститут електродинаміки НАН України, Київ, 2014)
The new mathematical model of nonlinear resistance of electro-spark load of discharge-pulse installations for volumetric electro-erosive dispersion (VEED) of layer of current-conducting granules in a dielectric liquid is developed. The transients in a discharge circuit of the reservoir capacitor of such installations are investigated with use of such model. The comparative analysis of changed in a time characteristics of a discharge circuit of the capacitor (electric resistance of electro-spark load, voltage drop on this load, rate of rise of the discharge current and its descent rate and power consumed in load) is carried out at modeling of electro-spark load by linear electric resistance and nonlinear one. It is shown, that with changing of available electric energy factor of the reservoir capacitor at its oscillatory discharge on electro-spark load the expediency of its modeling by nonlinear resistance increases. References 11, figures 6, tables 3.